Performance in golf putting - Karlsen, J. (2010)
Putting, which accounts for about 40 - 45 % of shots in elite golf, is a complex skill. To perform in putting an elite player needs to master green reading, putter aim and technique. Mental skills, equipment and strategy may also affect performance. Although several research papers have been published on the subject of putting, only a few focus specifically on putting performance. The aim of the thesis is to investigate different factors affecting performance in golf putting for elite players, and to compare the importance of those factors.